2021
DOI: 10.1182/blood.2020009617
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib in treatment-naive chronic lymphocytic leukemia

Abstract: Acalabrutinib has demonstrated significant efficacy and safety in relapsed chronic lymphocytic leukemia (CLL). The efficacy and safety of acalabrutinib monotherapy was evaluated in a treatment-naïve CLL cohort of a single-arm phase 1/2 clinical trial (ACE-CL-001). Adults were eligible for enrollment if chemotherapy was declined or deemed inappropriate due to comorbidities (N = 99). Patient demographics included a median age of 64 years and 47% with Rai stage III/IV disease. Acalabrutinib was administered orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…Long-term data from the phase 2 ACE-CL-001 study reaffirmed that acalabrutinib monotherapy for patients with treatment-naïve and R/R CLL provided durable responses with a favorable safety profile, with no new safety concerns reported (14,15). Several clinically relevant AEs considered to be associated with BTK inhibition in the clinical setting appear to be present at a low frequency in patients treated with acalabrutinib.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Long-term data from the phase 2 ACE-CL-001 study reaffirmed that acalabrutinib monotherapy for patients with treatment-naïve and R/R CLL provided durable responses with a favorable safety profile, with no new safety concerns reported (14,15). Several clinically relevant AEs considered to be associated with BTK inhibition in the clinical setting appear to be present at a low frequency in patients treated with acalabrutinib.…”
Section: Discussionmentioning
confidence: 94%
“…The median age of the patients with treatment-naïve CLL in this study was 64 years (range, 33-85) (14); and 66 years (range, 42-85) for patients with R/R CLL (20% of whom were aged ≥75 years) (15). In treatment-naïve patients, the most common AEs of any grade were diarrhea (51%), headache (45%), upper respiratory tract infection (44%), arthralgia (42%), and contusion (42%) (14). Any-grade and grade ≥3 severity AEs of clinical interest included infection (84% and 15%, respectively), bleeding event (66%/3%), and hypertension (22%/11%) (14).…”
Section: Adverse Events Associated With Btk Inhibitor Therapy Observed In Clinical Trialsmentioning
confidence: 97%
See 1 more Smart Citation
“…6,7 Treatment discontinuations because of adverse events in longer-term analyses of a phase II clinical trial of acalabrutinib monotherapy in previously untreated or relapsed or refractory CLL were reported in 6% and 11% of patients, respectively, at the median follow-up of 53 and 41 months, respectively. 22,23 Acalabrutinib has also demonstrated efficacy and tolerability in ibrutinib-intolerant patients with CLL. 24 This phase III trial prospectively compared the efficacy and safety of acalabrutinib with ibrutinib in patients with previously treated CLL to test the hypothesis that acalabrutinib was noninferior to ibrutinib in PFS with improved tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…There were more discontinuations due to AEs with ibrutinib (21%) than acalabrutinib (15%) [83]. Finally, the long-term results of the phase I/II study in the untreated CLL population confirmed a very good safety profile, with less than 10% of patients discontinuing treatment due to an adverse event [84].…”
Section: Acalabrutinibmentioning
confidence: 71%